2018
DOI: 10.11114/ijsss.v6i6.3300
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence (IPV) in Zambia: Socio-demographic Determinants and Association with Use of Maternal Health Care

Abstract: This study used the 2013-2014 Zambia Demographic and Health Survey (ZDHS) data to examine, on one hand, the socio-demographic characteristics associated with intimate partner violence (IPV) and, on the other hand, the relationship between IPV and maternal health care (place of delivery and ANC visits) utilization. The findings indicate that women’s characteristics including marital status, household wealth, witnessing parental violence and attitudes justifying wife beating were significantly associated with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…Our study has both limitations and strengths. One limitation is that the data from the DHS may underestimate the prevalence and extent of IPV due to underreporting, respectively social desirability [100,101]. Further, the cross-sectional nature of the study design does not permit fortitude of causality between variables.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Our study has both limitations and strengths. One limitation is that the data from the DHS may underestimate the prevalence and extent of IPV due to underreporting, respectively social desirability [100,101]. Further, the cross-sectional nature of the study design does not permit fortitude of causality between variables.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…10 But some research found that there is no significant association between IPV and utilization of antenatal care services in Zambia. 11 Present study aimed to assess the impact of interpersonal violence on utilization of antenatal care by women of Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…Republic of Congo (10), Ethiopia (19), Ghana (24), India (26), Malawi (16), Rwanda (12), Nigeria (20), Haiti (27), Zambia (17,28). The available literature suggests that alcohol consumption can weaken mental and physical function and cause in delity and aggressive behaviour (17).…”
Section: Emotional Violencementioning
confidence: 99%